„Hagyomány–Identitás–Történelem–2018 [From Church Founders to the Prohibited and Tolerated Pastoral Care Church History Volume on the Legacy of the Reformation]”, Réka Kiss–Gábor Lányi (Eds.), L’Harmattan, Budapest, 2019, 480 p., ISBN 978-963-414-570-7 - László NÉMETH (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2020)
“The process through which we assimilate our past contributes to and shapes our identity: it is a burdensome heritage that determines, sets tasks and sets a direction, but it is also a treasure we can be proud of.” – said András Gér at the opening of the Tradition, Identity and History (HIT2018) conference held on 25–26 October 2018. According to the coverage of the www.reformatus.hu portal, the synod advisor of the Reformed Church in Hungary (MRE) also emphasized that: “We must face what is behind us and understand why we have become what we are! As a result, we proudly but humbly assume our identity among our fellow human beings.”